The Influence of Product Quality, Product Design, and Brand Image on Purchase Decisions for Viva Cosmetic Products in Batam - Marcelina, Marcelina; Saputra, Asron (Universitas Batanghari, 2024)
In today's advanced era, many from various circles, especially among young people who are currently very concerned about their appearance to look neat, and attractive, especially for women whose lives are related to beauty and beauty in themselves. The business world in the beauty sector is experiencing a fairly rapid increase, as a result of the high number of purchases in the world of beauty, all companies in the beauty sector are competing to create attractive products and have the attractiveness to be able to encourage consumers to purchase these products.